Edward Armitage Robinson 1921 – 2013. Issue 4 (December 2015) - Lock, J.
Summary Edward Armitage Robinson (1921 – 2013) was a noteworthy collector of plants, particularly Cyperaceae, in Central Africa. An account of his career is given, with lists of species named after him or described from his collections.